A role of KIT receptor signaling for proliferation and differentiation of rat stem Leydig cells in vitro. (15th March 2017) - Liu, Shiwen; Chen, Xiaomin; Wang, Yiyan; Li, Linxi; Wang, Guimin; Li, Xiaoheng; Chen, Haolin; Guo, Jingjing; Lin, Han; Lian, Qing-Quan; Ge, Ren-Shan
Abstract: In the testis, KIT ligand (KITL, also called stem cell factor) is expressed by Sertoli cells and its receptor (c-kit, KIT) is expressed by spermatogonia and Leydig cells. Although KITL-KIT signaling is critical for the spermatogenesis, its roles in Leydig cell development during puberty are not clear. In the present study, we investigated effects of KITL on stem Leydig cell proliferation and differentiation. Using an in vitro culture system of seminiferous tubules from Leydig cell-depleted testis, we found that KITL increased the proliferation activity of putative stem Leydig cells at higher concentration (10 and 100 ng/ml). Low concentration (1 ng/ml) of KITL significantly induced the differentiation of stem Leydig cells via increasing the expression level of steroidogenic acute regulatory protein ( Star ). In contrast, higher concentration (100 ng/ml) of KITL inhibited the differentiation of stem Leydig cells via inhibiting the steroidogenic enzyme ( Cyp11a1, Cyp17a1, and Hsd17b3 ) expression levels. We cultured rat progenitor Leydig cells with KITL for 48 h and did not find any influence of KITL on the proliferation and androgen production of these cells. In conclusion, KITL is a growth factor that regulates the development of the stem Leydig cell. Highlights: Kit ligand has biphasic effects on stem Leydig cell development. Low concentration of Kit ligand stimulates the differentiation of stem Leydig cells. High concentration of Kit ligand stimulates the proliferation of stem Leydig cells. Kit ligand acts via PI3 kinase signaling.